Fungi as an efficient mycosystem for the synthesis of metal nanoparticles: progress and key aspects of research - Yadav, Alka; Kon, Kateryna; Kratosova, Gabriela; Duran, Nelson; Ingle, Avinash P; Rai, Mahendra (Biotechnology letters, 2015)
Nanotechnology is an emerging cutting-edge technology, which involves interdisciplinary subjects, such as physics, chemistry, biology, material science and medicine. Different methods for the synthesis of nanoparticles have been discussed here. Although physical and chemical methods have been successfully used to synthesize nanoparticles, the use of hazardous chemicals and synthesis at high temperature is a matter of concern. Hence, there is a necessity to develop eco-friendly techniques for the synthesis of nanoparticles. Biosynthesis of nanoparticles by fungi, bacteria, actinomycetes, lichen and viruses have been reported eco-friendly. Moreover, the fungal system has emerged as an efficient system for nanoparticle synthesis as fungi possess distinctive characters including high wall binding capacity, easy to culture and simpler biomass handling, etc. In this review, we have discussed fungi as an important tool for the fabrication of nanoparticles. In addition, methods and mechanism for synthesis of nanoparticles and its potential applications have also been discussed.
Keywords: Nanoparticles; technologie zelené chemie; Fungi; kovové nanočástice; houby; Metal Nanoparticles; Green chemistry; Nanotechnology; Green Chemistry Technology; Biosynthesis; Biotechnology; nanotechnologie; biotechnologie